2004
DOI: 10.1677/erc.1.00818
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive gene expression profiling of anaplastic thyroid cancers with cDNA microarray of 25 344 genes

Abstract: Little is known about the genetic mechanisms of anaplastic thyroid cancer (ATC). This is the most virulent of all human malignancies, and it is believed to result from transformation of differentiated thyroid cancers. To identify a set of genes involved in the development of ATC, we investigated expression profiles of 11 cell lines derived from ATC using a cDNA microarray representing 25 344 genes. Semi-quantitative RT-PCR experiments carried out for some genes that had shown altered expression on the microarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 23 publications
6
43
0
Order By: Relevance
“…In addition, the analysis related to the dedifferentiation process confirmed over-and underexpression of genes previously described to indicate poor prognosis for thyroid tumors (Rocha et al, 2003;Onda et al, 2004;Motti et al, 2005;Pallante et al, 2005;Sorrentino et al, 2005;Zou et al, 2005; Table 4). …”
Section: Discussionsupporting
confidence: 74%
“…In addition, the analysis related to the dedifferentiation process confirmed over-and underexpression of genes previously described to indicate poor prognosis for thyroid tumors (Rocha et al, 2003;Onda et al, 2004;Motti et al, 2005;Pallante et al, 2005;Sorrentino et al, 2005;Zou et al, 2005; Table 4). …”
Section: Discussionsupporting
confidence: 74%
“…Nucleophosmin nuclear overexpression in colon adenoma/ carcinoma seems also to be associated with adenoma/carcinoma progression (Nozawa et al, 1996). It has been shown that NPM overexpression was present in several human solid tumours, including gastric cancer (Tanaka et al, 1992), colon cancer (Nozawa et al, 1996), bladder cancer (Tsui et al, 2004), prostate cancer (Subong et al, 1999), thyroid cancer (Onda et al, 2004), and ovary cancer (Zhang, 2004). Interestingly, a recent review reported that NPM overexpression in tumour cells led to increased proliferation and inhibition of apoptosis and was involved in human tumorigenesis (Grisendi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has linked excessive NPM to cellular transformation and ontogenesis (Pulford et al, 2001). Nucleophosmin overexpression is frequently found in human cancers, including cancers of the stomach (Tanaka et al, 1992), colon (Nozawa et al, 1996), bladder (Tsui et al, 2004), prostate (Subong et al, 1999), thyroid (Onda et al, 2004), ovary (Zhang, 2004), and myeloid and lymphoid cells (Schnittger et al, 2005). It has been shown that overexpression of NPM in bladder cancer is independently associated with cancer recurrence and progression to more advanced stages, suggesting that NPM overexpression is an important prognostic indicator for bladder cancer recurrence (Tsui et al, 2004).…”
mentioning
confidence: 99%
“…For the comparison, five normal thyroid samples were served as a control in SQ-PCR. To adjust the amount of transcribed cDNA, GAPDH was selected as an internal control and SQ-PCR experiments were carried out as previously described, after adjustment of the amount of template cDNA (Onda et al, 2004a). The primer sequences for GAPDH were 5 0 -ggaaggtgaaggtcggagt-3 0 (forward) and 5 0 -tgggtggaatcatattggaa-3 0 (reverse).…”
Section: Semiquantitative Rt -Pcrmentioning
confidence: 99%
“…Recently, we investigated the gene expression profile of anaplastic thyroid cancer cell lines (ACLs) with cDNA microarray analysis (Onda et al, 2004a) and found the novel gene alterations that related to ATC/ACL carcinogenesis. The results of microarray analysis showed that haemoglobin beta (HBB) gene significantly decreased expression in ACLs, compared to the expression of normal thyroid gland.…”
mentioning
confidence: 99%